2002
DOI: 10.1046/j.1532-5415.2002.50027.x
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Optimum End‐of‐life Care for Minority Patients

Abstract: Although major efforts are underway to improve end-of-life care, there is growing evidence that improvements are not being experienced by those at particularly high risk for inadequate care: minority patients. Ethnic disparities in access to end-of-life care have been found that reflect disparities in access to many other kinds of care. Additional barriers to optimum end-of-life care for minority patients include insensitivity to cultural differences in attitudes toward death and end-of-life care and understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
166
2
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(171 citation statements)
references
References 160 publications
(234 reference statements)
1
166
2
2
Order By: Relevance
“…20,34,35 Nevertheless, we did not find support for religiousness as a mediator of racial/ethnic differences in ACP. Several possible explanations exist.…”
Section: Discussionmentioning
confidence: 38%
“…20,34,35 Nevertheless, we did not find support for religiousness as a mediator of racial/ethnic differences in ACP. Several possible explanations exist.…”
Section: Discussionmentioning
confidence: 38%
“…The paper that, in the estimation of this reviewer, holds the most promise for interpolation into policy and practice in the UK, is one written by three US MDs, Krakauer, Crenner and Fox (Krakauer et al 2002). Reviewing over 150 papers, the authors avoid the pitfalls of becoming bogged down in the review process itself and provide thoughtful discussion on the barriers to optimum end-of-life care for minority patients.…”
Section: A Discussion Of Terms and Terminologymentioning
confidence: 99%
“…In their study on barriers to optimum end-of-life care for minority patients, Krakauer et al (2002) point to the fact that African Americans prefer aggressive life-sustaining treatment more often than European Americans. The authors discuss issues of mistrust and medical racism, elaborated in their review, as contributing factors.…”
Section: A Discussion Of Terms and Terminologymentioning
confidence: 99%
“…5 Prior studies showing ethnic cultural differences over advance care planning, life support, and other aspects of dying further supported our assumption. 3,8,[10][11][12] Our interview study revealed occasional beliefs that may characterize Americans in general, some beliefs that may characterize only certain ethnic groups or genders, and many beliefs that may characterize only particular individuals.…”
Section: Discussionmentioning
confidence: 99%
“…We assumed that culture-the values a group uses to interpret shared experiences and transmits across generations 2,3 -influences those beliefs. 1,[4][5][6][7][8][9][10] We reasoned that, because death is a universal human experience, every culture must address its meaning. 5 Prior studies showing ethnic cultural differences over advance care planning, life support, and other aspects of dying further supported our assumption.…”
Section: Discussionmentioning
confidence: 99%